Characterization of phenolic compounds in mature Moroccan Medjool date palm fruits (Phoenix dactylifera) by HPLC-DAD-ESI-MS - Khallouki, Farid; Ricarte, Írvila; Breuer, Andrea; Owen, Robert (Journal of food composition and analysis, 2018)
The purpose of this study was to determine the phytochemical composition of the rarely studied mature Moroccan Medjool dates (Phoenix dactylifera). The amount of total phenolic compounds, determined by analytical high performance liquid chromatography (HPLC) in combined 2% aqueous acetic acid and methanol extracts was 61.3mg/100g wet weight. The phenolic compounds, definitively identified by high performance liquid chromatography-diode array detection-electrospray ionization-mass spectrometry (HPLC-DAD-ESI-MS) were (I) chelidonic acid, (II) 3, 4-dihydroxybenzoic acid, (III) dicaffeoyl shikimik acid isomer-1, (IV) p-hydroxybenzoic acid, (V) caffeic acid glucoside, (VI) ferulic acid diglucoside, (VII) dicaffeoyl shikimik acid isomer-2, (VIII) vanillic acid, (IX) dicaffeoyl shikimik acid isomer-3, (X) p-hydroxybenzaldehyde, (XI) caffeoyl shikimik acid-1, (XII) caffeoyl shikimik acid-2, (XIII) caffeoyl shikimik acid-3, (XIV) vanillin, (XV) p-coumaric acid, (XVI) trans-ferulic acid, (XVII) cis-ferulic acid, (XVIII) taxifolin rhamnoside, (XIX) apigenin-C-diglucoside, (XX) rutin, (XXI) luteolin-7-O-rhamnoglucoside, (XXII) quercetin-3-O-galactoside, (XXIII) quercetin-3-O-glucoside, (XXIV) luteolin-7-O-rhamnoglucoside isomer, (XXV) kaempferol-3-O-rhamnoglucoside, (XXVI) isorhamnetin-3-O-rhamnoglucoside, (XXVII) chrysoeriol-7-O-rhamnoglucoside, (XXVIII) isorhamnetin-3-O-glucoside, (XXIX) chrysoeriol-7-O-rhamnoglucoside isomer, (XXX) chrysoeriol-7-O-glucoside, (XXXI) quercetin, (XXXII) luteolin, and chrysoeriol (XXXIII). The major components were chelidonic acid at 29.44mg/kg and di-caffeoyl shikimic acid isomers at 9.49mg/kg wet weight, respectively. Consumption of Moroccan Medjool date palm fruits should contribute to a healthy diet.